2013
DOI: 10.1080/07448481.2013.833932
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, Anxiety, and Depressive Distress: Evidence for the Mediating Role of Negative Automatic Thoughts and Anxiety Sensitivity

Abstract: Abstract.Objective: This study assessed a mediational model in which negative automatic thoughts and anxiety sensitivity were hypothesized to mediate the relationship between perfectionism cognitions and depressive and anxiety symptoms. Participants: Participants were undergraduate students from an urban Canadian university. The data were collected from July 2009 to August 2010. Methods: In a cross-sectional evaluation, 992 undergraduate participants completed questionnaires that assessed perfectionism cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
1
29
0
3
Order By: Relevance
“…Furthermore, the PCI has been employed in multiple randomized-controlled trials which have demonstrated that Perfectionists can achieve benefits in depressed and anxious moods (Radhu et al, 2012a) as well as cortical inhibition (Radhu et al, 2012b), by way of cognitive-behavioral therapy and mindfulness practice. Furthermore, the uneven proportion in this study is representative of the typical prevalence found at this university, in which a previous recruit of N = 992 participants yielded N = 248 (~25%) maladaptive perfectionists with the same screening procedure (Pirbaglou et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the PCI has been employed in multiple randomized-controlled trials which have demonstrated that Perfectionists can achieve benefits in depressed and anxious moods (Radhu et al, 2012a) as well as cortical inhibition (Radhu et al, 2012b), by way of cognitive-behavioral therapy and mindfulness practice. Furthermore, the uneven proportion in this study is representative of the typical prevalence found at this university, in which a previous recruit of N = 992 participants yielded N = 248 (~25%) maladaptive perfectionists with the same screening procedure (Pirbaglou et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…"I should never make the same mistake twice" and "I must be efficient at all times") in the previous week on a 5-point Likert scale. The PCI has demonstrated adequate validity and reliability and correlational analyses have revealed strong associations with trait perfectionism, psychological distress, and depressive-anxious symptoms (Flett et al, 2007;Flett et al, 2011;Pirbaglou et al, 2013). Furthermore, there has been no gender difference in mean PCI scores found (Flett et al, 1998).…”
Section: Screeningmentioning
confidence: 95%
See 1 more Smart Citation
“…In this line, there is strong relationship between stress, anxiety with perfectionism [21]. Pirbaglou et al also in a recent study evaluating 992 undergraduate participants confirmed the role of anxiety sensitivity and negative automatic thoughts in mediating the association between perfectionistic cognitions and anxiety symptoms [22].…”
Section: Discussionmentioning
confidence: 87%
“…As it is well known, one of the most useful exercises in cognitive psychotherapy is when the patient is asked to examine his or her automatic thoughts. As research suggest, negative automatic thoughts could affect not just maladaptive ways of thinking, risky behavior (Choon, 2015) but also serious mental diseases as depression (Hjemdal, 2013), anxiety (Pirbaglou et al, 2013), addiction or even adult ADHD (Mitchell et al 2013). If the patient wants to overcome his symptoms, he must learn how to use selfcontrol over automatic associations and thoughts (Gonsarkolare et al, 2010).…”
Section: Control As Regulation Automatization and Programmingmentioning
confidence: 99%